KELAS KHUSUS BACA TULIS QURAN DI MTS SIROJUL IKHSAN DESA PALASARI CIJERUK BOGOR - Siti Alawiyah Putri; Muhamad Fahmi Ali; Asep Anwar Sanusi (Pastabiq : Jurnal Pengabdian Kepada Masyarakat, 2023)
Special classes for reading and writing the Qur'an have a large role in helping students learn to read the Qur'an well and correctly. In this way, apart from being able to read it, it is hoped that students will also be able to understand and be able to practice the teachings of Islam in their lives. This activity aims to determine the effect of special classes for reading and writing the Qur'an on students' learning outcomes in basic competency in reading the Qur'an. Data collection takes the form of observation and documentation. The subjects are students from MTs Sirojul Ikhsan, Palasari Village, Cijeruk, Bogor. The results of this activity showed a significant influence between special classes for reading and writing the Qur'an on learning outcomes for basic competency in reading the Qur'an.